4.5(7.6z+3)-3=

Simple and best practice solution for 4.5(7.6z+3)-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.5(7.6z+3)-3= equation:


Simplifying
4.5(7.6z + 3) + -3 = 0

Reorder the terms:
4.5(3 + 7.6z) + -3 = 0
(3 * 4.5 + 7.6z * 4.5) + -3 = 0
(13.5 + 34.2z) + -3 = 0

Reorder the terms:
13.5 + -3 + 34.2z = 0

Combine like terms: 13.5 + -3 = 10.5
10.5 + 34.2z = 0

Solving
10.5 + 34.2z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-10.5' to each side of the equation.
10.5 + -10.5 + 34.2z = 0 + -10.5

Combine like terms: 10.5 + -10.5 = 0.0
0.0 + 34.2z = 0 + -10.5
34.2z = 0 + -10.5

Combine like terms: 0 + -10.5 = -10.5
34.2z = -10.5

Divide each side by '34.2'.
z = -0.3070175439

Simplifying
z = -0.3070175439

See similar equations:

| lnx+x=5 | | 5x^2+6x+13=0 | | 9y-11=-10x+5 | | 7.6(4.5z-3)+3= | | y+8=7x | | ln(m)=.5(ln(x^2-y)) | | x/2-29=22 | | -5(-3)(-7)(-1)= | | 7(x+3)+2=7x+9 | | 3x^2/3x | | 0.18(2x)=29.5 | | 8x+10y=170 | | 0.18(2x)=59 | | y-15x=3 | | -17.3-m=22.8 | | 5+30=x+6 | | 2xy+10=90 | | x^9=-7 | | 3x+39=0 | | 3i*3i= | | -0.9(7.5w-6)-9= | | i*3i= | | 9(x-4)+x=10(x-4)+4 | | .02=15.4 | | -5x+3.6=2.1-4x | | 7.5(-0.9w-9)-6= | | x^2+2=3y | | 3x^3+5x-24=0 | | 4x+8x=2(6x-12) | | 4(8-5x)=25 | | -8+22=15x-2-14x | | (8a-5x)2= |

Equations solver categories